The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1055/s-2006-957787
|View full text |Cite
|
Sign up to set email alerts
|

Pectic Polysaccharides from Roots ofGlycyrrhiza uralensis: Possible Contribution of Neutral Oligosaccharides in the Galacturonase-Resistant Region to Anti-Complementary and Mitogenic Activities

Abstract: Digestion with endo-alpha-(1-->4)-polygalacturonase liberated the enzyme-resistant region (PG-1c) as an active site of the anti-complementary and mitogenic pectic polysaccharide (GR-2IIc) from Glycyrrhiza uralensis. Partial acid hydrolysis of PG-1c resulted in acidic oligosaccharides, and methylation analysis and GC-MS analysis of the acidic oligosaccharides suggested that PG-1c comprised a rhamnogalacturonan core such as -->2)-Rha-(1-->4)-GalA-(1-->2)-Rha-(1-->4)-GalA-(1-->-->4)-GalA-(1-->4) as the acidic moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The component sugar analysis and the reaction to b-glucosyl Yariv reagent indicated that PN-IIa might contain arabinogalactan and acidic polysaccharides. These results were typical in anti-complementary pectic polysaccharides found in Bupleurum falcatum, 30) Glycyrrhiza uralensis 31) and Panax ginseng.…”
Section: Discussionsupporting
confidence: 69%
“…The component sugar analysis and the reaction to b-glucosyl Yariv reagent indicated that PN-IIa might contain arabinogalactan and acidic polysaccharides. These results were typical in anti-complementary pectic polysaccharides found in Bupleurum falcatum, 30) Glycyrrhiza uralensis 31) and Panax ginseng.…”
Section: Discussionsupporting
confidence: 69%
“…immunologically active polysaccharides isolated from G. uralensis roots (Shimizu et al 1992;Kiyohara et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The licorice used in PWS (Glycyrrhiza uralensis [GRZ]) is honey roasted and is a different species of licorice (Glycyrrhiza glabra L.) than that found in most English texts. One in vitro study, 23 citing G. uralensis as a clinically useful treatment for inflammation, allergy, and gastric ulcer, showed that samples of the root had anticomplementary and mitogenic activities. Another study, 24 with mice, reported that liver microsomal cytochrome P450 induction by GRZ had much less effect than glycyrrhetinic acid (also found in G. glabra) alone.…”
Section: Ping Wei San Clinical and Pharmacologic Effectsmentioning
confidence: 99%